The reliability estimate of throw pedestrian using traditional and computer methods - Avramović Zoran Ž.; Cvijan Milorad R.; Smailović Emir Z. (Tehnika, 2020)
The development of information technology has created conditions for development and implementation of software for the simulation of traffic accidents. Among large number software tools which are being used in Europe, software PC Crash stand out. In this paper comparative analysis of distance throw of pedestrian using the traditional and contemporary methods was realized. The distance throw of pedestrian using the software PC Crash, depending on the height and weight of pedestrian is showed. By using of statistical methods difference between traditional and contemporary methods was researched.